Catastrophic rockslides and the geomorphology of the Hunza and Gilgit River Valleys, Karakoram Himalaya - Hewitt, Kenneth (ERDKUNDE, 2001)
The paper describes 79 rock slide-rock avalanches discovered in the Hunza and Gilgit river basins, mainly deposits of prehistoric mass movements. They occur at all elevations, and in each of the main geological terranes and clima-geomorphic environments. Examples from the Naltar and Batkor valleys, at Nomal, Baltit-Sumayar and near Pasu in Hunza, are described. The nature of such mass movements is briefly discussed. Their deposits are distinguished as coarse cataclastic ’fragmentites’ with angular clasts in all grain sizes. Samples of rubble and matrix materials show homogeneous lithology derived from bedrock outcropping on nearby valley walls. Deposit morphologies and facies characteristics record large scale unity of emplacement. Run out of debris is often strongly modified by rugged valley topography, creating distinctive constructional landforms. Most examples formed large cross-valley barriers on the rivers. They have constrained fluvial development, ice margin deposition, and related landforms in the late Quaternary. Vast quantities of valley-fill sediments, and typical fluvial zone landforms, mainly record epicycles of aggradation and trenching related to the landslide barriers. This includes most of the well-known lacustrine beds, sediment fans, river terrace systems, stepped river profiles, and occasional rock bed gorges. The features reflect major geomorphic consequences of post-glacial rock wall instability. However, until now, the more accessible rock avalanches were mistaken for glacial deposits, and employed as such in glacial and landform histories. The identification of these and other cross-valley barriers as post-glacial landslides, indicates a need to revise Quaternary, as well as geomorphic, interpretations.